Problem Gambling in Hong Kong and Macao Etiology, Prevalence and Treatment - Chan, Chi Chuen; Li, William Wai Lim; Leung, Eugene Chung Ip; SpringerLink (Online service) (Singapore : Springer Singapore (Imprint), 2016)
This book critically examines the psychology of gambling in Hong Kong and Macao. Covering the history of gambling and its development in the two jurisdictions, it highlights the prevalence and status quo of problem gambling, the theoretical perspectives on the etiology of gambling disorder, and the treatment of problem gambling. The book also introduces a personality and pathways development model of Chinese problem gamblers and concludes with outlooks on the future of gambling in Hong Kong and Macao.
Chapter 1: The History of Gambling in Hong Kong and Macao. Chapter 2: The State of Gambling in Hong Kong and Macao -- Chapter 3: The Personality of Problem Gamblers in Hong Kong and Macao -- Chapter 4: The Etiology of Problem Gambling -- Chapter 5: The Treatment of Problem Gamblers in Hong Kong and Macao -- Chapter 6: The Review on CBT and a Multi-modal Treatment Model for Problem Gamblers -- Chapter 7: The Challenges and the Future for Problem Gambling in Hong Kong and Macao.
Keywords: Applied psychology; Community and Environmental Psychology